PENGARUH TOTAL ASET, LIABILITAS, DAN INVESTASI PADA ENTITAS ASOSIASI TERHADAP KINERJA TRANSPORTASI LOGISTIK PADA PT ANGKASA PURA II PERIODE 2018 - 2022 - Gunawan, Adnan Teguh (Jurnal Pijar, 2025)
This research aims to analyze the influence of total assets, total liabilities and investment in associated entities on total company equity, with a case study of PT Angkasa Pura II during the 2018–2022 period. A quantitative approach is used through multiple regression analysis methods, with secondary data in the form of the company's annual financial reports. The research results show that total assets have a significant positive influence on total equity, reflecting the important role of assets in increasing company value through optimizing operational capacity. On the other hand, total liabilities show a significant negative effect on equity, which indicates that a high debt burden can reduce the company's financial stability. Meanwhile, investment in associated entities did not have a significant impact on total equity, which can be explained by the long-term nature of the investment and the impact of the COVID-19 pandemic which affected the company's fund allocation priorities. Simultaneously, the total assets, liabilities and investment variables contribute 99% to the variation in total equity, as shown by the Adjusted R² value. This research supports capital structure theory and investment theory, which emphasizes the importance of balanced financial management in creating company sustainability. Apart from providing a theoretical contribution to the financial literature, the results of this research also provide practical implications for asset management strategies, reducing liabilities, and optimizing investment in the strategic infrastructure sector. These findings are relevant to support more effective financial decision making in facing long-term challenges.